2014
DOI: 10.1186/scrt529
|View full text |Cite
|
Sign up to set email alerts
|

Relative genomic stability of adipose tissue derived mesenchymal stem cells: analysis of ploidy, H19 long non-coding RNA and p53 activity

Abstract: IntroductionMesenchymal stem cells (MSCs) are multipotent and have been derived from various tissues. Although MSCs share many basic features, they often display subtle tissue specific differences. We previously demonstrated that bone marrow (BM) MSCs frequently become polyploid in culture. This tendency was mediated by a reduction in the expression of H19 long non-coding RNA during the transition from a diploid to a polyploid state.MethodsMSCs were derived from both BM and adipose tissue of mice and expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Here, we found that H19 expression decreased significantly during osteogenic differentiation of human ASCs. To the best of our knowledge, only one study showed reduced expression of H19 in ASCs as compared with BMSCs [38]; however, no report exists regarding H19 expression during osteogenesis of ASCs. This discrepancy might be explained by evidence showing that H19 expression is regulated in a tissue- and cell-specific manner during embryogenesis [39].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that H19 expression decreased significantly during osteogenic differentiation of human ASCs. To the best of our knowledge, only one study showed reduced expression of H19 in ASCs as compared with BMSCs [38]; however, no report exists regarding H19 expression during osteogenesis of ASCs. This discrepancy might be explained by evidence showing that H19 expression is regulated in a tissue- and cell-specific manner during embryogenesis [39].…”
Section: Discussionmentioning
confidence: 99%
“…In BM MSCs, polyploidy appeared to be a more stable state than diploidy as diploid BM MSCs were significantly more tumorigenic following subcutaneous administration, and expressed much higher levels of H19. The correlation between H19 expression and the tendency of BM MSCs to become polyploid was further substantiated in another recent publication that compared the genomic stability of BM MSCs to that of ASCs [18] . Altogether, it was found that 76% (13 out of 17 cell preparations) of mouse BM MSCs preparations, demonstrated a polyploid phenotype compared to only 9% polyploidy (3 out of 32 cell preparations) of ASCs.…”
Section: Why Are Ascs More Gnomically Stable and Less Tumorigenic Thamentioning
confidence: 73%
“…The recent study [20] suggested that in some instances the opposite is true, namely tetraploidy is necessary for p53 wild type cells to remain non-tumorigenic. It was additionally found that the basal p53 activity, evident by the RNA expression of various p53 target genes, was significantly higher in ASCs compared to BM MSCs [18] . Interestingly, three different DNA damage stresses (UV eradiation, oxidative stress by H 2 0 2 and doxorubicin) all resulted in a significant p53 activation in both tetraploid BM MSCs and in ASCs demonstrating the presence of a wild type p53 in these cells.…”
Section: Is P53 Activity Involved In Ascs Increased Genomic Stability?mentioning
confidence: 94%
See 2 more Smart Citations